Causes and Results of Repeated Operations in Iatrogenic Lesions of the Biliary System - Allan Abdiev, Imashov Ulan, Toktosunov Arsen, Rahatbek Omorov, Syimykbek Saparov, Niazbek Mamatov, Tugolbai Tagaev, (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Iatrogenic injuries, resulting from medical interventions, often necessitate repeat surgeries, which pose significant challenges for patients and health-care systems. This retrospective study aimed to evaluate the occurrence and outcomes of various procedures for iatrogenic injuries, focusing on liver and bile duct traumas. Methods: The study included 110 patients aged 34–72 years who underwent reoperation due to surgical complications at two leading medical centers in Bishkek, Kyrgyzstan, from 2015 to 2023. Of these, 21 (19.3%) patients required additional surgery, primarily due to iatrogenic harm to the liver and bile ducts during initial operations, predominantly laparoscopic cholecystectomies for cholelithiasis. The diagnostic approach incorporated clinical assessment, imaging studies, and laboratory analysis. Results: Reoperations varied according to injury type and severity, with immediate operations conducted on 17 (81%) patients and delayed reconstructive surgeries performed on 4 (19%) patients. Post-reoperation complications occurred in 5 (23.8%) patients, and the average hospital stay was 14 days. The study reported a 4.8% mortality rate, highlighting the significant risks associated with surgical management of iatrogenic injuries. Conclusion: Effective management of these injuries requires a comprehensive approach that prioritizes patient safety, quality of care, and efficient resource utilization. Ongoing professional development, adherence to guidelines, and continued research on prevention and innovative surgical techniques are essential to reduce the occurrence of iatrogenic injuries and improve patient outcomes.